THE MODEL OF MANAGING THE IT SERVICES CATALOG - Левикін, В. М.; Юр’єв, І. О. (Science-based technologies, 2017)
The IT services catalog is a key source of information about the IT services provided to the business by the IT service provider. It provides business with an up-to-date, reliable and complete picture of the available IT services, their details and statuses. The IT services catalog should contain the details and dependencies of all IT services that are operated, decommissioned or under development. The availability of a quality catalog of IT services at the enterprise leads to a reduction of misunderstanding between the IT service and the end users of IT services. Based on these tasks, a model for managing the catalog of IT services was developed. The model provides strict types of possible references to the catalog of IT services. The model was implemented as an algorithm for managing the catalog of IT services. A particular feature of this algorithm is the periodic monitoring of the state of IT services.